Investigation of characteristics of powder at press surpasses 3000 ton - Rosfazila Mamat (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
This project is carried out to investigate characteristic an iron powder at pressure beyond 3000 tons. The effects of high load and pressure on a compacted powder were investigated. A cube shape was produced using pressing machine prior to use as an explosive compaction. Type of explosive that will be used in this study is EMULEX. It is an explosive that available in Malaysia and suitable for this experiment.